Correction: The Diversity and Geographical Structure of Orientia tsutsugamushi Strains from Scrub Typhus Patients in Laos. - Rattanaphone Phetsouvanh; Piengchan Sonthayanon; Sasithon Pukrittayakamee; Daniel H Paris; Paul N Newton; Edward J Feil; Nicholas P J Day (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0004024.].